Leave Management Information System using InsideDPS Software for the Efficiency of Human Resources Management - Sentot Imam Wahjono; Anna Marina; Ismail Rasulong; Fam Soo Fen (Kinetik: Game Technology, Information System, Computer Network, Computing, Electronics, and Control, 2020)
The purpose of this research is to study the management information system and the benefits of InsideDPS software. The study was designed with an embeded mixed method, namely quantitative-qualitative-quantitative. The questionnaire as a quantitative tool was built based on previous research (MSQ), distributed to 250 employees and 198 sets of analyzed multiple linear regression. The questionnaire was distributed 2 times, before and after qualitative research. Interviews, observation and document collection were held with informants for HR managers, IT managers, and selected employees. This study found evidence that MIS InsideDPS software can support HRD performance improvement which is also supported by increased employee satisfaction. The technical implication of the findings of this study is the need for a wider web-based MIS application in the company